Knowledge through internal and external organizational networks: a perspective of social capital and absorptive capacity - Santos, Tainá Alves dos (2022)
Some studies have already pointed out the trade-off between internal and external sources for developing firms absorptive capacity, considering that special attention may be needed regarding the relationship between shared knowledge and breadth of knowledge among individuals (Ramayah et al., 2020). While absorptive capacity can help to explain why the internal and external relationships of a firm impact innovation performance, alternative explanations seem possible considering how these firms share knowledge internally. In this sense, this dissertation filled three identified gaps. First, absorptive capacity is a construct explored and studied through many perspectives in the last decades. Although some bibliometrics and literature reviews are being done since Volberda et al. (2010), it is unclear which path research is heading on this topic. Second, the literature on networks and knowledge is also extensive, and it does not seem clear which subjects are most relevant to be studied in this field of research. Third, no studies were found examining the influence of a firm's absorptive capacity and knowledge gathered from its internal and external relationships on innovation performance. Some research identified the effects of external and internal relationships on innovation performance, such as Maurer et al. (2011) and Najib & Kiminami (2011), but the drivers that led to these outcomes are still unclear. In this sense, firms with the same networks to obtain knowledge may present different innovation results, indicating that there may be mechanisms related to the knowledge flow that differentiate these companies. I argue that firms introducing innovations based on internal and external knowledge will present a different ability to exploit knowledge because of their absorptive capacities. To explore the role of absorptive capacity and internal and external organizational networks in companies' innovation performance, I developed this dissertation with three studies in sequential order. Methodologically, a bibliometric study of cocitation and coupling was carried out in Study 1. Then, I chose to use topic modeling to explore the field of knowledge networks and innovation in Study 2. Finally, I used PLS-SEM approach and PROCESS macro in Study 3, using data collected from startups in Brazil by survey.